PERENCANAAN KARIR FRESH GRADUATE BERDASARKAN TEORI LIFE SPAN - Ramadhani, Lusi (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2023)
Every individual generally has to prepare a career plan, in order to achieve a career that is of course in accordance with the talents, interests and abilities that he has. However, the fact that we have often encountered lately is that there are still many fresh graduates who feel worried when they finish. Therefore this research will look at how the career planning of fresh graduates is reviewed based on the life span theory. The method used is descriptive qualitative analysis with interviews with fresh graduates. Conducting interviews carried out several general steps, namely. 1. Identify the person being interviewed. 2. Determine the type of interview to be used. 3. During the interview, record the questions and answers. 4. Take brief notes during the interview. 5. Find a quiet and suitable place to conduct the interview. 6. Obtain consent from the interviewee to participate in the research. 7. Flexible inquiry. 8. Use sub-questions for additional information. 9. Be polite and professional during the interview. The results of the research revealed that the two informants already had good and well-planned career plans, this can be seen from both aspects of self-knowledge, attitudes and skills. The two informants were able to explain their career plans after fresh graduates and what concrete steps they would take